Interaksi Persaingan Usaha dan Perlindungan Data: Menelaah Bundeskartellamt v. Facebook - Siti Shalima Safitri (Komisi Pengawas Persaingan Usaha, 2023)
Big Data brings new challenges in terms of competition law and data protection. The intersection of data regulation with competition law is due to the fact that most digital products are paid for by users and consumers online by providing their personal data. The author will discuss whether data breaches can be considered a violation of competition law, in light of the German Facebook case in which the Bundeskartellamt investigated whether alleged violations of data protection provisions could mean that Facebook abused its dominant position in the digital market. The research uses a normative legal method with a literature study. The results of the research show that abuse of the digital market cannot be drawn from mere dominance or unfair contract terms, but rather there needs to be a combination of market power and the absence of other options for contract terms. If Facebook users are given more choices regarding how their data is collected, they will be deemed to give voluntary consent under data protection law. This research can serve as a guideline for Indonesian lawmakers and competition authorities to adjust competition regulations, especially in the era of digitalization.